Small Rho GTPases and the Effector VipA Mediate the Invasion of Epithelial Cells by Filamentous Legionella pneumophila - Prashar, Akriti; Ortiz, María Eugenia; Lucarelli, Stefanie; Barker, Elizabeth; Tabatabeiyazdi, Zohreh; Shamoun, Feras; Raju, Deepa; Antonescu, Costin; Guyard, Cyril; Terebiznik, Mauricio R. (Frontiers in Cellular and Infection Microbiology, 2018)
Legionella pneumophila (Lp) exhibits different morphologies with varying degrees of virulence. Despite their detection in environmental sources of outbreaks and in respiratory tract secretions and lung autopsies from patients, the filamentous morphotype of Lp remains poorly studied. We previously demonstrated that filamentous Lp invades lung epithelial cells (LECs) and replicates intracellularly in a Legionella containing vacuole. Filamentous Lp activates β1integrin and E-cadherin receptors at the surface of LECs leading to the formation of actin-rich cell membrane structures we termed hooks and membrane wraps. These structures entrap segments of an Lp filament on host cell surface and mediate bacterial internalization. Here we investigated the molecular mechanisms responsible for the actin rearrangements needed for the formation and elongation of these membrane wraps and bacterial internalization. We combined genetic and pharmacological approaches to assess the contribution of signaling downstream of β1integrin and E-cadherin receptors, and Lp Dot/Icm secretion system- translocated effectors toward the invasion process. Our studies demonstrate a multi-stage mechanism of LEC invasion by filamentous Lp. Bacterial attachment to host cells depends on signaling downstream of β1integrin and E-cadherin activation, leading to Rho GTPases-dependent activation of cellular actin nucleating proteins, Arp2/3 and mDia. This mediates the formation of primordial membrane wraps that entrap the filamentous bacteria on the cell surface. Following this, in a second phase of the invasion process the Dot/Icm translocated effector VipA mediates rapid membrane wrap elongation, leading to the engulfment of the filamentous bacteria by the LECs. Our findings provide the first description of Rho GTPases and a Dot/Icm effector VipA regulating the actin dynamics needed for the invasion of epithelial cells by Lp.